QIBLA DIRECTION ACCURACY ANALYSIS BASED ON ASTRONOMY (GOOGLE EARTH), PERSPECTIVE OF ISLAMIC LAW - Wahyuni, Sri; Samsuddin, Samsuddin; Hamzah, Ekawati (Universitas Islam Negeri Alauddin Makassar, 2022)
Qibla is defined as the building of the Ka’bah or the direction of Muslims in carrying out a worship, especially prayer, so we need a method that can be used as a guide in determining the direction of Qibla in worship. This study aims to determine the accuracy of the Qibla direction of mosques in Tanete Riattang and Tanete Riattang Barat Districts as measured using astronomy (Google Earth), and the study of Islamic law views the measurement of Qibla direction using astronomy. The method used in this study is a qualitative method, namely the method used to process ideas, reviews and views of experts, as well as descriptive qualitative data analysis methods, namely comparing theoretical studies and realities in the field. The results showed that the method of determining the Qibla direction used in this study using the Google Earth software is relatively easy, very accurate and efficient, but people prefer to determine the Qibla direction by using a compass and also by using the sun's shadow which is known to have quite a difference significant (less accurate). Therefore, the involvement and concern of the government, in this case the Ministry of Religion, as well as competent parties in the field of astrology (determination of the Qibla direction) are needed. Qibla is the direction of the Muslims in worship, therefore we must try our best to determine the direction of Qibla as accurately as possible, considering the growing development of intellectual civilization, especially in the field of astronomy. So that in the future uniformity of direction in worship can be achieved.